Does school privatization improve educational achievement? Evidence from Sweden's voucher reform - Anders Böhlmark; Mikael Lindahl (Institute for the Study of Labor (IZA), 2008)
This paper evaluates general achievement effects of choice and competition between private and public schools at the nine-year school level by assessing a radical voucher reform that was implemented in Sweden in 1992. Starting from a situation where the public schools essentially were monopolists on all local school markets, the degree of privatization has developed very differently across municipalities over time as a result of this reform. We estimate the impact of an increase in private enrolment on short, medium and long-term educational outcomes of all pupils using within-municipality variation over time, and control for differential pre-reform and concurrent municipality trends. We find that an increase in the private school share moderately improves short-term educational outcomes such as 9th-grade GPA and the fraction of students who choose an academic high school track. However, we do not find any impact on medium or long-term educational outcomes such as high school GPA, university attainment or years of schooling. We conclude that the first-order short-term effect is too small to yield lasting positive effects.
urn:nbn:de:101:1-2008100922
Keywords: I22; 330; Private schooling; choice; competition; educational achievement; Allgemeinbildende Schule; Privatschule; Voucher; Wettbewerb; Bildungsniveau; Schweden